Documenting the Armenian Genocide Essays in Honor of Taner Akçam - Kühne, Thomas; Rein, Mary Jane; Mamigonian, Marc A. (Palgrave Studies in the History of Genocide, 2024)
"This book of essays by leading scholars on the Armenian Genocide is a fitting tribute to Taner Akçam and a major contribution to the field he has helped to define. Embodying the virtues of his pathbreaking work, they present both micro- and macro-perspectives on one of the twentieth-century's defining events." -A. Dirk Moses, City College of New York, USA "This book is a major contribution to the field of Armenian Genocide Studies. The interdisciplinary aspect of the book - that ranges from gender violence, humanitarianism, the role of cinema, and memoirs, to the economic dimension of the genocide, activism in genocide studies, and historiographic analysis - provides new perspectives on the Armenian Genocide and its repercussions. The book is a must read to all those interested in understanding the different facets of the Armenian Genocide." -Bedross Der Matossian, University of Nebraska-Lincoln, USA This open access book brings together contributions from an internationally diverse group of scholars to celebrate Taner Akçam's role as the first Turkish intellectual to publicly recognize the Armenian Genocide. As a researcher, lecturer, and mentor to a new generation of scholars, Akçam has led the effort to utilize previously unknown, ignored, or under-studied sources, whether in Turkish, Armenian, German, or other languages, thus immeasurably expanding and deepening the scholarly project of documenting and analyzing the Armenian Genocide. Thomas Kühne is Strassler Colin Flug Professor of Holocaust History and Director of the Strassler Center for Holocaust and Genocide Studies at Clark University, USA. Mary Jane Rein is Executive Director of the Strassler Center for Holocaust and Genocide Studies at Clark University, USA. Marc A. Mamigonian is Director of Academic Affairs at the National Association for Armenian Studies and Research, USA.